Impact of health education in improving awareness about Methicillin resistant Staphylococcus aureus in health care professionals of tertiary healthcare centre in India - Rana, Priyanka; Sule, Poorva Abhishek; Kulkarni, Vrushali Vishal; Ubale, Milind R.; Jaitpal, Varun Milind (International Journal of Research in Medical Sciences, 2019)
Background: Methicillin resistant Staphylococcus aureus (MRSA) is a major pathogen causing morbidity and mortality in hospital setup. Healthcare professionals (HCPs) colonized by MRSA, play a key role in transmission of this organism to the patients. Compliance of the HCPs with sanitary guidelines is fundamental to prevent nosocomial Infections. Hence, imparting education and creating awareness is the first step towards this. The aim of this study was to determine baseline knowledge about MRSA in healthcare professionals (HCPs). The further aim of the study was to assess the impact of health education on HCPs. Methods: A total of 104 participants, including 54 nurses and 50 doctors, were surveyed using pre-validated questionnaire, regarding MRSA colonization, modes of transmission, high risk areas in hospital, isolation policy, disinfection and treatment. The survey was followed by a health education session on MRSA. Thereafter a post-test questionnaire was administered to study the impact of the health education session. Results: The study sample of 104 respondents comprised of 50 doctors (48%) and 54 nurses (52%). It was found that baseline awareness regarding MRSA was lesser in the nursing staff as compared to doctors. Statistically significant positive impact of the health education session on all the HCPs was observed when paired t-test was applied. Various challenges expressed by the participants in prevention of MRSA transmission were noted. Conclusions: Due to suboptimal awareness noted in HCPs, educational programs should be conducted to bridge the gap in knowledge and perception of HCPs to prevent spread of MRSA.